A COMPARISON OF COCONUT INDUSTRY DEVELOPMENT IN SILANG AND NORTH MINAHASA - Soewignyo, Tonny (JBE (Journal of Business and Economics); Volume 7 No.2, 2008 JBE UNKLAB, 2008)
This paper primarily aimed to compare coconut industry in Silang, Cavite Province, Philippines and North Minahasa, North Sulawesi Province, Indonesia to enhance the livelihood and local income. The study was conducted from July to August 2008 in Silang rural areas and North Minahasa rural areas using descriptive survey method and the research data originated from the collection and analysis of primary and secondary data. The results generally indicate that income generating from coconut farming currently very low. Coconut farmers in Silang produce young coconut while in North Minahasa copra and old coconut. There is no value added created from the coconut trees. To increase income of coconut plantation farmers in Silang practice intercropping and livestock while in North Minahasa intercropping only.